MENELISIK KESIAPAN SUMBER DAYA MANUSIA NON KESEHATAN DALAM MENDUKUNG PELAYANAN RUMAH SAKIT DI ERA NEW NORMAL - Suwira, I Wayan; Martini, Ida Ayu Oka (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2021)
The readiness of Human Resources is an important element of the success of the Hospital organization in providing good health services to Covid-19 patients. Non-Health Workers are competent workers who must be ready to face the Services in the New Era. The purpose of this study is to see how the readiness of non-health human resources in supporting hospital services in the New Era is normal. The type of research used is a case study using a qualitative descriptive research approach with data collection techniques: in-depth interviews and documentation. Data processing in this study uses thematic analysis. The results of the study indicate that socialization or fair information about the Covid-19 disease intensively, carrying out continuous evaluations and ensuring the implementation of the Director's policy regarding the application of health protocols at work and the budgeting policy for the provision of Personal Protective Equipment greatly affect the Readiness of Non-Health Human Resources in supporting services. Hospitals in the New Era are normal. This is in accordance with the technical guidelines for hospital services during the adaptation period of new habits issued by the Indonesian Ministry of Health in 2020 that hospital administrators prepare service management according to national health protocol standards by prioritizing health and safety by preventing and controlling the transmission of COVID-19 so that can provide protection for human resources in hospitals. It is recommended that regularly socialize the application of health protocols on an ongoing basis, carry out monitoring and evaluation in stages.